2018
DOI: 10.1093/ntr/nty139
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Public Smoking Bans on Social Inequalities in Children’s Exposure to Tobacco Smoke at Home: An Equity-Focused Systematic Review

Abstract: There are substantial social inequalities in children's secondhand smoke (SHS) exposure in many countries. Both hypotheses on the effect of smoke-free legislation on children's SHS exposure at home, the displacement hypothesis and the social diffusion hypothesis, did not take social inequalities into account. Up to now, only few studies analysed the effects of smoke-free legislation on social inequalities in children's SHS exposure at home. Public smoking bans had overall no negative impact on social inequalit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…46 For SHS exposure in households, Nanninga et al reviewed nine studies and argued that, whereas there was little evidence to support whether smoke-free policies reduced socioeconomic inequalities in SHS exposure in the household, their capacity to increase inequalities was unlikely. 47 This paper extends this literature in the context of a recent tobacco control legislation in the Canadian province of Quebec. This province (8.5 million inhabitants) has had among the highest levels of SHS exposure at home across the 10 Canadian provinces (5.7% versus the national average of 3.9% in 2014).…”
Section: Introductionmentioning
confidence: 70%
“…46 For SHS exposure in households, Nanninga et al reviewed nine studies and argued that, whereas there was little evidence to support whether smoke-free policies reduced socioeconomic inequalities in SHS exposure in the household, their capacity to increase inequalities was unlikely. 47 This paper extends this literature in the context of a recent tobacco control legislation in the Canadian province of Quebec. This province (8.5 million inhabitants) has had among the highest levels of SHS exposure at home across the 10 Canadian provinces (5.7% versus the national average of 3.9% in 2014).…”
Section: Introductionmentioning
confidence: 70%
“…We used the PROGRESS‐Plus framework, and previous inequality‐focused systematic reviews, to inform our categorization of which groups under each PROGRESS‐Plus criterion would be defined as “more advantaged” or “less advantaged.” 8,28–30 We considered “more advantaged” groups as follows: urban (place of residence, people living in urban areas often have more proximal access to healthcare and other amenities), White (race/ethnicity), employed full‐time (occupation), male (gender or sex), majority religion (religion), more education (Education), less deprived—for area based measures—or higher income level (SES), being married (social capital), and being older (PLUS). We categorized being older as “more advantaged” as evidence suggests older adults have fewer barriers to accessing primary care and are more likely to be offered weight management intervention in routine practice 31–33 .…”
Section: Methodsmentioning
confidence: 99%
“…29 Open access have been used in systematic reviews of various intervention types since. [30][31][32][33][34][35] Even where there is heterogeneity in measures used, Harvest plots allow for all available and relevant data to be used and presented. 29 36 37 Several study features can be graphically demonstrated on a single plot, such as study quality, statistical significance and sample size.…”
Section: Data Synthesis Narrative Synthesis and Harvest Plotsmentioning
confidence: 99%